The prolyl isomerase Pin1 stabilizes NeuroD during differentiation of mechanoreceptors - Zhao, Liqun; Fong, Steven H.; Yang, Qiaoyun; Jiang, Yun-Jin; Korzh, Vladimir; Liou, Yih-Cherng (Frontiers in Cell and Developmental Biology, 2023)
Pin1 plays vital roles in diverse cellular processes and pathological conditions. NeuroD is a differentiation and survival factor for a subset of neurons and pancreatic endocrine cells. Although multiple phosphorylation events are known to be crucial for NeuroD function, their mechanisms remain elusive. In this study, we demonstrate that zebrafish embryos deficient in Pin1 displayed phenotypes resembling those associated with NeuroD depletion, characterized by defects in formation of mechanosensory hair cells. Furthermore, zebrafish Pin1 interacts with NeuroD in a phosphorylationdependent manner. In Pin1-deficient cell lines, NeuroD is rapidly degraded. However, the protein stability of NeuroD is restored upon overexpression of Pin1. These findings suggest that Pin1 functionally regulates NeuroD protein levels by post-phosphorylation cis-trans isomerization during neuronal specification.